A Historical Overview of Mixed Martial Arts in China - Acevedo, William; Cheung, Mei (Revista de Artes Marciales Asiáticas, 2012)
Mixed martial arts (MMA) has become one of the fastest-growing combat sports in the twenty-first century, drawing millions of Pay-Per-View spectators since the inception of the Ultimate Fighting Championship (UFC) in 1993. Popular conceptions have credited the creation of MMA to Bruce Lee, a Chinese-American actor and martial artist who became an icon in the 1970s and who is still considered by many as a revolutionary figure in the field. This paper will present, in chronological order, examples of ancient Chinese martial arts concepts preceding the creation of modern MMA.